1982
DOI: 10.1002/aic.690280105
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of thermodynamic data by means of the multiresponse maximum likelihood principle

Abstract: ) dtThe system was first partitioned, giving two small loops and one large loop. LOOP 1 consisted of Eqs. III-9,III-10,111-13,III-14 and 111-20 in which Eqs. 111-9 and 111-10 are nonlinear. LOOP 2 was made up of Eqs. 111-18,111-24,111-26,111-30 and 111-31 all of which are linear. Once these blocks were isolated they were collapsed into single nodes leaving one large cycle, LOOP 3, consisting of all of the remaining equations.The constant kz was varied to make the system stiff. Solutions were obtained for k2 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…However, it should be noted that statistical methods that account for errors in the other measured variables can also be used (Kemeny et al, 1982). Given Np experimental data points of the PTxy type, one of the following different objective functions was minimized in order to evaluate the model parameters:…”
Section: Data-reduction Proceduresmentioning
confidence: 99%
“…However, it should be noted that statistical methods that account for errors in the other measured variables can also be used (Kemeny et al, 1982). Given Np experimental data points of the PTxy type, one of the following different objective functions was minimized in order to evaluate the model parameters:…”
Section: Data-reduction Proceduresmentioning
confidence: 99%
“…Ž . Kemeny et al, 1982. Kemeny et al 1982 examined manýś imilar functions; although they did not conclude that any one of them was markedly better than the others, their work showed that inclusion of weights led to consistently superior results.…”
Section: Binary Vapor-liquid Equilibrium Data Reductionmentioning
confidence: 97%
“…1968 , and of the VLE data-reduction method developed by Ž . Kemeny et al 1982 . The latter authors observed that thé complexity of calculations is ''considerably reduced'' by omitting the determination of the true values of the regressors.…”
Section: G Wgs G W G 21mentioning
confidence: 99%
See 1 more Smart Citation
“…the Reid vapor pressure) of the gasoline -oxygenate mixture is largely determined by the vapor pressure of the oxygenate. It is partly for this reason that largely C 5 result in a very slight increase in the Reid vapor pressure of a gasoline. Higher ethers such as tert-amyl methyl ether (TAME), diisopropyl ether (DIPE), and others, which are less volatile, have little effect on the Reid vapor pressure of the gasoline at the concentrations in which they are used, and may even result in a slight lowering.…”
Section: General Comments On the Vapor-liquid Equilibrium Of Oxygenatmentioning
confidence: 99%